Perlindungan Hukum Pengguna Jasa Pariwisata Parasailing Pantai Gunung Payung Kabupaten Badung - Ni Kadek Dewi Agustina; I Nyoman Gede Sugiartha; Luh Putu Suryani (Warmadewa Press, 2024)
Legal Protection of Parasailing Tourism Service Users is Legal Protection for tourism service users in the field of tourism services that protect the safety of tourists and protect the rights of tourists as users of parasailing tourism services. The formulation of the problem is How is the Legal Protection provided by Tourism Managers to consumers who use Parasailing Tourism Services at Gunung Payung Beach and How is the Responsibility of the Parasailing Tourism Services Manager at Gunung Payung Beach if an accident occurs. Based on Law Number 10 of 2009 concerning Tourism. This research uses Empirical research meditate with a statutory approach and interview techniques. The results of this study indicate the responsibility of the Gunung Payung Beach Parasailing Tourism Service Manager in the event of an accident in Parasailing Tourism activities based on Law Number 8 of 1999, namely Consumer Protection which protects the safety of tourists and protects their rights.